Prenormalization rounding in IEEE floating-point operations using a flagged prefix adder. - Burgess, N. (IEEE Transactions on VLSI systems)
This paper demonstrates how IEEE 754 floating-point standard compliant rounding can be merged with carry-propagate addition in floating-point unit (FPU) designs by using a novel adaptation of the prefix adder. The paper considers add/subtract, multiply, and SRT divide operations and demonstrates that in every case a generic rounding architecture based on a prefix adder with a small amount of additional logic is sufficient to cover all the rounding modes. Critical path analysis shows that the proposed architecture is compatible with contemporary pipelined FPU design practice, while using significantly less logic